2005
DOI: 10.21273/jashs.130.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Markers in Hazelnut: Isolation, Characterization, and Cross-species Amplification

Abstract: Three microsatellite-enriched libraries of the european hazelnut (Corylus avellana L.) were constructed: library A for CA repeats, library B for GA repeats, and library C for GAA repeats. Twenty-five primer pairs amplified easy-to-score single loci and were used to investigate polymorphism among 20 C. avellana genotypes and to evaluate cross-species amplification in seven Corylus L. species. Microsatellite alleles were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 37 publications
5
70
1
3
Order By: Relevance
“…Intrageneric cross-amplification of fescue SSR markers in grass gave 3.98 alleles per SSR locus (Saha et al 2006). These results suggest that our use of more distantly related bamboo species may have resulted in a higher number of alleles per SSR locus (Bassil et al 2005) and that the flanking region of the rice SSR markers may have been conserved and duplicated in these bamboo species (Chen et al 2002). Transferability, the ratio of amplified markers/tested markers Effect of SSR markers with different motif types Peakall et al (1998) reported that SSR markers can be classified into three different motif types, namely, pure, compound, and interrupted.…”
Section: Resultsmentioning
confidence: 75%
“…Intrageneric cross-amplification of fescue SSR markers in grass gave 3.98 alleles per SSR locus (Saha et al 2006). These results suggest that our use of more distantly related bamboo species may have resulted in a higher number of alleles per SSR locus (Bassil et al 2005) and that the flanking region of the rice SSR markers may have been conserved and duplicated in these bamboo species (Chen et al 2002). Transferability, the ratio of amplified markers/tested markers Effect of SSR markers with different motif types Peakall et al (1998) reported that SSR markers can be classified into three different motif types, namely, pure, compound, and interrupted.…”
Section: Resultsmentioning
confidence: 75%
“…Compared with other species, the number of microsatellites described for hazelnut is limited (18 microsatellites were described by Boccacci et al. 2005 and 33 microsatellites by Bassil et al. 2005a,b), indicating a need for continued efforts to develop new molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…2005). In addition, a set of 51 SSR markers has been developed (Bassil et al. 2005a,b, Boccacci et al.…”
mentioning
confidence: 99%
“…(Cabe et al 2005;Hokanson et al 2001), apricot (Prunus armeniaca L.) (Romero et al 2003), peach [Prunus persica (L.) Batsch] (Aranzana et al 2002;Testolin et al 2000) grape (Vitis vinifera L.) (Dangl et al 2001;Fatahi et al 2003;Martin et al 2003), and pistachio (Pistacia vera L.) (Ahmad et al 2003). In hazelnut, simple sequence repeat (SSR) markers have been developed by Bassil et al (2005) and Boccacci et al (2005).…”
Section: Introductionmentioning
confidence: 99%